IDENTIFIKASI GAYA BELAJAR DALAM UPAYA PENINGKATAN HASIL BELAJAR PESERTA DIKLAT PRAJABATAN - Nur Endah Widyastuti (Jurnal Litbang Sukowati : Media Penelitian dan Pengembangan, 2022)
Internal and external factors influence the results of training. By using the mixed method, this study aimed to investigate the influence of learning style on learning results among 26 participants of Pre-service Training Group II Special Appointment of Non-Honorary in Sragen Regency in 2020. Data were obtained from questionnaire instruments, interview guides, and document studies. Quantitative data were processed with a simple linear regression test using SPSS 17. Statistical tests obtained a significance value of 0.428, indicating that learning style does not affect the results. However, Qualitative Analysis illustrated that information about learning styles helped participants and teachers optimize the classroom learning process.